Prevalence of mental disorders among adolescents in German youth welfare institutions - Nuetzel Jakob; Goldbeck Lutz; Schmid Marc; Fegert Joerg M (BMC, 2008)
Abstract Objective Multiple psycho-social risk factors are common in children and adolescents in youth welfare, especially in residential care. In this survey study we assessed the prevalence of behavioral, emotional symptoms and mental disorders in a German residential care population. Methods 20 residential care institutions including 689 children and adolescents (age 4 - 18 years; mean 14.4; SD = 2.9) participated. A two-step design was performed. First, the children and adolescents and their residential caregivers answered a standard symptom checklist (CBCL/YSR). For those participants scoring more than one standard deviation above the mean of their German population reference group, a standardized clinical examination was performed to specify an ICD-10 diagnosis. Results The study population reached high average scores in almost all scales and subscales of the CBCL and YSR (mean CBCL total score T = 64.3, SD = 9.7, Median = 66.0). The prevalence of mental disorders according to the diagnostic criteria of ICD-10 was 59.9%, with a predominance of externalizing and disruptive disorders. High rates of co-morbidity were observed. Conclusion Children and adolescents in youth welfare and residential care are a neglected high risk population. Providing adequate psychiatric diagnosis and multimodal treatment for this group is necessary.